2019
DOI: 10.1038/s41467-019-11507-z
|View full text |Cite
|
Sign up to set email alerts
|

The essential elements for the noncovalent association of two DNA ends during NHEJ synapsis

Abstract: One of the most central questions about the repair of a double-strand DNA break (DSB) concerns how the two free DNA ends are brought together — a step called synapsis. Using single-molecule FRET (smFRET), we show here that both Ku plus XRCC4:DNA ligase IV are necessary and sufficient to achieve a flexible synapsis of blunt DNA ends, whereas either alone is not. Addition of XLF causes a transition to a close synaptic state, and maximum efficiency of close synapsis is achieved within 20 min. The promotion of clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 43 publications
(67 reference statements)
4
70
0
Order By: Relevance
“…It is suggested that DNA‐PKcs is not required for the formation of either FS or CS. This latter model explains the evolutionarily central synaptic role of the core NHEJ factors, Ku70, Ku80, XRCC4, Lig4 and XLF 24 …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is suggested that DNA‐PKcs is not required for the formation of either FS or CS. This latter model explains the evolutionarily central synaptic role of the core NHEJ factors, Ku70, Ku80, XRCC4, Lig4 and XLF 24 …”
Section: Introductionmentioning
confidence: 91%
“…PAXX and MRI have not been implicated in this model because their functions have not been identified 7 . Another model proposed by Lieber’s group 24 suggests that there are two major structural complexes formed during the NHEJ synapsis. Ku70, Ku80, XRCC4 and Lig4 form the flexible synaptic (FS) complex, where XRCC4 and Lig4 bind to each DSB through interaction of Lig4 with Ku heterodimer.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, recent work in a human reconstitution of NHEJ also suggest that XLF filaments are not necessary for end synapsis. 37 Therefore, we considered a model in which the two tails of the XLF dimer enable the formation of a Ku-XLF-Ku bridge 33 that is required to synapse DNA ends. Using synthetic tandem dimers of XLF, we generated asymmetric XLF dimers to show that a single KBM within an XLF dimer is sufficient to promote NHEJ in both Xenopus egg extract (FIG 4B-C) and in mammalian cells (FIG 6B).…”
Section: Recruitment Of Xlf To Dsbs Is Necessary But Not Sufficient Fmentioning
confidence: 99%
“…There are several potential explanations for this unanticipated observation. First, recent findings suggest that DNA-PK may be dispensable for synapsis formation during NHEJ 37 . Accordingly, repair of “simple” DSBs in G1 phase may have a reduced reliance on DNA-PK, whereas repair of more “complex” DSBs in S phase may require DNA-PK, possibly in partnership with the nuclease Artemis 3840 .…”
Section: Discussionmentioning
confidence: 99%